EFFECT OF FOLIAR SPRAYING WITH ZINC, ASCORBIC AND GIBBERELLIC ACIDS ON GROWTH, YIELD OF EGGPLANTS GROWN UNDER UNHEATED PLASTIC HOUSE - Abdul Jabbar Al-Hubaity; Hussien J. M. Al-Bayati; Waleed B. A. Al-Lelah (Mesopotamia Journal of Agriculture)
This study was carried out during winter growing season 2011-2012 to study the effect of foliar spray with three levels of each zinc (0,20,40 mgl-1), ascorbic acid (0,100,200 mgl-1) and GA3 (0,25,50 mgl-1) in order to improve the vegetative growth and yield components of egg plants(Benecia F1cv.). The study was arranged in RCBD with three replication. The plants were sprayed three times separately for each treatment at one month intervals between each spray beginning from first flowering date. Results indicated a significant increase in the number of branches, dry matter(%), while non-significant increase was seen in plant length, chlorophlly (%), leaf area, number of leaves, number of fruits, fruits weight, early yield and total yield per unit area by spraying plant with zinc. Whereas, ascorbic acid treatment caused a non-significant increase in chlorophyll (%), dry matter (%), number of branches and fruits weight. On the other hand, spraying with GA3 resulted in a significant increase in plant length, number of branches plant -1, but revealed non-significant increase in the remnant traits excluding fruit weight which reduced by GA3 treatments as compared with control treatment. Correlation analysis exhibited a positively significant correlation between the total yield per unit area with each of number of fruits plant-1, leaf area plant-1, number of leaves plant-1, plant length at probability0.01,andwithfruitweightatprobability 0.05.